2019
DOI: 10.11591/ijphs.v8i2.20061
|View full text |Cite
|
Sign up to set email alerts
|

Integrating palliative care and hospice services in long term care: an eightfold path health policy analysis

Abstract: It is evident in the literature that as near end of life approaches, health expenditure increases. The rehospitalization and underutilization of palliative and hospice services add to the burgeoning health cost. There is a lack of support for patients with advanced illness in long-term care facilities. This paper aims to provide a comprehensive review of the problem and assess alternatives to reduce readmission among patients with advanced disease and those who are at the end of life.  This paper adapted Barda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Interest in spirituality and spiritual care has increased in recent years, and a growing amount of literature reveals that it is seen in the nursing profession as important to patient health and healing (Hvidt et al, 2020;Weathers et al, 2016) but that it is still not well understood or frequently practiced (Chen et al, 2020;McSherry, 2020). While there has been a significant amount of spiritual care research in palliative care nursing (Nolan et al, 2011;Tan Jr., 2019) and in the chaplaincy literature (Poncin et al, 2019), limited research has been identified addressing spiritual issues in the acute care setting (Cone & Giske, 2017;Giske & Cone, 2015), nursing homes (Dewittea et al, 2021;Gordon et al, 2020), mental health (Holmberg et al, 2021;Patterson et al, 2018), paediatrics (Fazlollahi et al, 2022) or from the patient perspective (Best et al, 2022;Cone & Giske, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Interest in spirituality and spiritual care has increased in recent years, and a growing amount of literature reveals that it is seen in the nursing profession as important to patient health and healing (Hvidt et al, 2020;Weathers et al, 2016) but that it is still not well understood or frequently practiced (Chen et al, 2020;McSherry, 2020). While there has been a significant amount of spiritual care research in palliative care nursing (Nolan et al, 2011;Tan Jr., 2019) and in the chaplaincy literature (Poncin et al, 2019), limited research has been identified addressing spiritual issues in the acute care setting (Cone & Giske, 2017;Giske & Cone, 2015), nursing homes (Dewittea et al, 2021;Gordon et al, 2020), mental health (Holmberg et al, 2021;Patterson et al, 2018), paediatrics (Fazlollahi et al, 2022) or from the patient perspective (Best et al, 2022;Cone & Giske, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%